Cara Kilat Pengajaran Makkiyyah-Madaniyyah di PTKIN Melalui Konsep Berpikir Jalaluddin Al-Suyuti - Imam Masrur (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2019)
The aim of this research is to provide prompt method of Makkiyyah-Madaniyyah teaching in Islamic University. It explores Makkiyah-Madaniyyah concept of Jalaluddin al-Suyuti on his works al-Itqan, and combines the concept with other media. This research applies library research. The finding shows that teaching method of Makkiyyah-Madaniyyah focused on Jalaluddin al-Suyuti’s parts or verses mapping combined with Ahmad Hatta’s Quran Tafsir Perkata can support more effective understanding, more comprehensive, free from misunderstanding of determining Makkiyyah-Madaniyyah